The impact of COVID-19 on police officer wellness - Sytsma, Victoria A. (Policing and society, 2024)
Disaster policing requires considerably more effort than working under normal conditions, thereby exacerbating existing threats to employee wellness. Research suggests that such working conditions may be harmful to physical and mental health outcomes, including increasing absenteeism. This study relies on personnel records from 3,398 police officers across 12 police services to determine the extent to which the COVID-19 pandemic impacted police officer work attendance and absenteeism, controlling for officer – and community-level characteristics. Results indicate that compared to the previous time-period, work attendance decreased during the COVID-19 pandemic and absenteeism increased. Data shows that a greater proportion of officers worked fewer days during the pandemic compared to the time-period before, and a smaller proportion worked a greater number of days. Multilevel mixed effects models indicate that COVID-19 largely contributed to decreasing attendance and increasing absenteeism beyond the effects of community conditions and officer demographics.